Profil Sikap Ilmiah Peserta Didik Dalam Pembelajaran Fisika di SMA YPPK Teruna Bakti Jayapura - Sakliressy, Maura Trynovita; Sunarno, Widha; Nurosyid, Fahru (Universitas PGRI Semarang, 2021)
Physics learning aims to provide provision experience and skill process, increase the creativity and scientific attitude of students. A scientific attitude is needed in learning science, including physics, because when students have a high scientific attitude, understanding of the concept and learning outcomes will increase. The purpose of this article is to look at the profile of students' scientific attitudes on the dimensions of attitudes, critical attitudes to facts, critical thinking, respect for data / facts, open thinking and cooperation in learning physics. This study aims to describe the scientific attitude profile of the XII grade students of SMA YPPK Teruna Bakti. The method used in this research is quantitative quantitative. The data was collected through a non-test instrument in the form of a questionnaire based on four of the six dimensions of scientific attitudes according to Harlen. The test was conducted on 35 students. The test results showed that the total average level of mastery was 73%. Scientific attitude per dimension, for curiosity dimension 75%, critical thinking dimension 72%, critical thinking dimension to data / facts 67%, open thinking dimension 77% and cooperation 74%.Keywords: Scientific Attitude, Assessment, Physics